(untitled) (Journal of Forest and Livelihood, 2024)
This paper examines the contribution of Nepalese Community Forestry in social change process in two central hills districts of Nepal. Analysis of data indicates improvement in forest management, decision making, representation of poor and women in forest management and utilisation, awareness on economic and ecological contributions of forests. Debates and discussions have increased as regards roles and responsibilities of users as well as mechanisms for gender-sensitive, poverty-focused and equity-based forest management activities. All these factors are contributing to achieve sustainable management of forest resources, to improve the living condition of people and to promote non-coercive social transformation.